Assessing and Communicating the Value of Biomedical Research: Results From a Pilot Study. (October 2017) - Guthrie, Susan; Krapels, Joachim; Adams, Alexandra; Alberti, Philip; Bonham, Ann; Garrod, Bryn; Esmond, Sarah; Scott, Caitlin; Cochrane, Gavin; Wooding, Steven
Abstract : Purpose: Assessing the impact of research requires an approach that is sensitive both to the context of the research and the perspective of the stakeholders trying to understand its benefits. Here, the authors report on a pilot that applied such an approach to research conducted at the Collaborative Center for Health Equity (CCHE) of the University of Wisconsin School of Medicine and Public Health. Method: The pilot assessed the academic impact of CCHE's work; the networks between CCHE and community partners; and the reach of CCHE's programs, including an attempt to estimate return on investment (ROI). Data included bibliometrics, findings from a stakeholder survey and in-depth interviews, and financial figures. Results: The pilot illustrated how CCHE programs increase the capacity of community partners to advocate for their communities and engage with researchers to ensure that research benefits the community. The results illustrate the reach of CCHE's programs into the community. The authors produced an estimate of the ROI for one CCHE program targeting childhood obesity, and values ranged from negative to positive. Conclusions: The authors experienced challenges using novel assessment techniques at a small scale including the lack of comparator groups and the scarcity of cost data for estimating ROI. This pilot demonstrated the value of research from a variety of perspectives—from academic to community. It illustrates how metrics beyond grant income and publications can capture the outputs of an academic health center in a way that may better align with the aims of the center and stakeholders.